moking out tobacco use from sports - Abd Razak, Dzulkifli (1996)
Yesterday, May 31, was the 1996 World NoTobacco Day. It is a day for all individuals, communities and nations to take stock of what is happening around them as far as tobacco use, especially cigarette smoking, is concerned. This time around, the theme is "Sports and Arts without Tobacco." The World NoTobacco Day was initiated by the World Health Organization (WHO) to look into the progress made by each member state in the attempt to eliminate smoking habits among their population. This is perhaps the only day in the year that the tobacco issue is widely addressed. For Malaysia, being a member of WHO, this event has special significance and this was demonstrated last year when the government promulgated and implemented a series of measures to curb the spread of smoking among Malaysians, especially in the young. The Ministry of Health in particular, has been the prime mover in such efforts.